The Religious Content of the Apostasy Movement - Al-Habradi, Hadi Qaed (Journal of Humanities & Social Sciences, 2019)
After the death of the Prophet Mohammed (Peace be upon Him), tribes have apostatized and so the movement of apostasy has had a significant impact on Islam. This research has attempted to deal with the religious content of the apostate movement, which was not dealt with previously by researchers. It defined the movement of apostasy, its causes, the types of apostates; and how to eliminate it. The researcher concluded that the main reason for this movement is the religious motive, and this motive was the basic one for others. He recommended that the Islamic history should be read objectively based on reliable sources. He recommended also that we should not make hasty judgments based on prejudicial views of the enemies of Islam.